Pattern and Outcome of Respiratory Disease in Dhaka Shishu Hospital: A One Year Analysis (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: Respiratory diseases are one of the major causes of childhood morbidity and mortality in Bangladesh. It is also a leading cause of hospital admission. The aim of this study is to analyze the pattern of respiratory disease admissions in a tertiary care hospital in a developing country.Methods: We carried out a retrospective study on patients that presented with respiratory condition from January 2016 to December 2016.The medical records of patients admitted in the department of pediatric respiratory medicine unit (Pulmonology) over one-year period were reviewed. Information obtained included demography, diagnosis, mean duration of hospital stay and outcome of illness.Results: Total 21 types of respiratory illness were categorized. The male to female patients ratio was 1.3:1. Among the patients 76.4% were less than five years old, 21.07% were between 5 and 9.9 years old, while 2.45% were 10 years and above. Pneumonia (54.41%) was the most common cases seen, followed by bronchiolitis (21.07%), PTB (2.94%), acute asthma (2.45%), pleural effusion (1.96%) and disseminated TB (1.96%). The median duration of admission was 12.9 days. Majority (93.6%) of admitted cases were discharged with advise, death was recorded in 2 (0.98%) children.Deaths occurred in children less than 5 years old, one with Bronchiolitis Obliterans Organizing Pneumonia and another with Tuberculosis.Conclusion: Pneumonia, bronchiolitis and TB were the leading respiratory diseases among children admitted in Dhaka Shishu Hospital.DS (Child) H J 2018; 34(1) : 36-40